2018
DOI: 10.1111/1750-3841.14103
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Quantitative Analysis of Ediphenphos Residue in Rice Using Surface‐Enhanced Raman Spectroscopy

Abstract: This study developed a surface-enhanced Raman spectroscopy (SERS) method for detection of ediphenphos in rice coupled with simple extraction protocol and gold nanorods on a portable Raman spectrometer. SERS is a rapid and accurate method which can be applied in agricultural grain safety inspection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…24−29 There are several research articles describing quantitative analysis of food products using Raman. 26,30−32 trace contaminants in milk, and Weng et al 31 reported quantitative analysis of ediphenphos residue in rice. Another group 24,25,33 reported the quantitation of TiO 2 in table sugar using Raman spectroscopy and also developed the flavonoidassisted microextraction method for TiO 2 detection.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24−29 There are several research articles describing quantitative analysis of food products using Raman. 26,30−32 trace contaminants in milk, and Weng et al 31 reported quantitative analysis of ediphenphos residue in rice. Another group 24,25,33 reported the quantitation of TiO 2 in table sugar using Raman spectroscopy and also developed the flavonoidassisted microextraction method for TiO 2 detection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to difficulties of ionizing TiO 2 in ICP-MS analysis, researchers developed new approaches for TiO 2 quantitation. One of the more recently developed methods for quantitation of food additives or toxic materials in food involves Raman spectroscopic methods. There are several research articles describing quantitative analysis of food products using Raman. , Tan et al described a single-drop Raman imaging technique for the analysis of trace contaminants in milk, and Weng et al reported quantitative analysis of ediphenphos residue in rice. Another group ,, reported the quantitation of TiO 2 in table sugar using Raman spectroscopy and also developed the flavonoid-assisted microextraction method for TiO 2 detection.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, SERS with mPEG-SH-coated GNRs, PLSR and PCA can detect pirimiphos-methyl residues in wheat with high sensitivity and good repeatability when coupled with the presented extraction method. Method detection limit (MDL) and reliable quantitation limit (RQL) were used to assess the limit-of-detection of the presented methodology [30]. MDL of pirimiphos-methyl residue in wheat was 0.0442 mg/L, and RQL was 0.1768 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Surface‐enhanced Raman scattering (SERS) is a sensitive and rapid detection method that shows great advantages in the ultrasensitive detection of trace chemicals (Weng et al., 2018; Yan et al., 2022; Zhang, Xue, et al., 2022; Zhu et al., 2022). For SERS detection, the electromagnetic enhancement has been reported as the main mechanism contributing to the SERS enhancement effect.…”
Section: Introductionmentioning
confidence: 99%